Efecto de dos niveles de sombra y nutrición sobre el crecimiento y desarrollo vegetativo en cacao (Theobroma cacao L.) clon CCN51 en la Provincia de Zamora Chinchipe - Espinosa Masa, Jorge Geovanny (2021)
Cocoa (Theobroma cacao L.) is one of the major export products in Ecuador and the average of national yield production is low (0,5 t/ha), compared to other countries which reaching 5 t/ha. Primary research on cocoa emerged a few years ago, however, in Ecuador, cocoa production is carried out under low-tech management, probably due to the lack of knowledge of the producers. Likewise, there is scarce information on the effect of fertilization and the use of shade for cocoa production in conditions of the Ecuadorian Amazon, therefore, this work aims to evaluate different levels of fertilization and the use of shade during growth and vegetative development in a recently established cocoa orchard. In the present study, clone CCN51 in the growth stage was used as plant material, the trial was established at the Experimental Station "El Padmi", in the province of Zamora Chinchipe. Four treatments were evaluated: T1= Control (no shade and no fertilization), T2= Fertilization (based on nutrient demand and supply), T3= Shade (using a mesh that prevents the passage of 80 % solar radiation) and T4= Shade - fertilization interaction. For this, morphological variables were evaluated including plant height, stem diameter, stem cross-sectional area (ASTT), shoot length, absolute and relative growth rate (TCA and TCR), number of metameres. Physiological variables were also measured: leaf area index (LAI), leaf chlorophyll concentration and leaf stomatal density. Soil pH and electrical conductivity were measured periodically. The effect of the treatments on the dependent variables was evaluated by ANOVA and a Tukey test of means (p=0.05). Although no significant effects of the treatments were found for most of the variables, fertilization increased plant height and metamer length as a consequence of the increase in growth rate. Shade favored leaf expansion and increased plant leaf area, as well as IAF. The results of this work suggest that nutrition and the reduction of solar radiation of cocoa can favor the growth of this crop from early stages, however, it is necessary to continue this study in the following stages of the crop to see its impact on productive variables. Key words: Theobroma cacao, fertilization, shading, incident solar radiation, vegetative growth